(untitled) (Scientific journal of the Fergana State University, 2023)
Development of a working sample of the SUM-18 (Sh (m-18) plant for processing vegetables and fruits to produce natural juice is discussed. The process of obtaining in the designed unit SUM-18 (ShҚM-18) a technologically natural, environmentally friendly product contained in vegetables and fruits consists of deeply saturating the raw materials in water vapor and extracting juice from it in an amount of 50-70% of the total volume.